2016
DOI: 10.1556/2006.5.2016.083
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Internet Gaming Disorder Scale – Short-Form (IGDS9-SF) in an Italian-speaking sample

Abstract: Background and aimsThe inclusion of Internet Gaming Disorder (IGD) in Section III of the fifth edition of the Diagnostic and Statistical Manual of Mental Disorders has increased the interest of researchers in the development of new standardized psychometric tools for the assessment of such a disorder. To date, the nine-item Internet Gaming Disorder Scale – Short-Form (IGDS9-SF) has only been validated in English, Portuguese, and Slovenian languages. Therefore, the aim of this investigation was to examine the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

26
119
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 148 publications
(149 citation statements)
references
References 45 publications
26
119
1
3
Order By: Relevance
“…The IGDS9-SF provided a valid and reliable measure of IGD with excellent diagnostic accuracy that can be used in for research and for diagnostic purposes among young adult male and female gamers. Overall, the results obtained in the present study corroborated prior validity studies on the IGDS9-SF (Monacis et al, 2016;Pontes and Griffiths, 2015;Wu et al, 2017).…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…The IGDS9-SF provided a valid and reliable measure of IGD with excellent diagnostic accuracy that can be used in for research and for diagnostic purposes among young adult male and female gamers. Overall, the results obtained in the present study corroborated prior validity studies on the IGDS9-SF (Monacis et al, 2016;Pontes and Griffiths, 2015;Wu et al, 2017).…”
Section: Discussionsupporting
confidence: 89%
“…The results of the EFA and CFA yielded statistically significant and relatively high factor loadings, further demonstrating that all items were adequate indicators of the IGD construct and that the scale had adequate psychometric properties, alongside a solid factor structure. In the original study, the IGDS9-SF showed adequate reliability (α = 0.87), whereas Cronbach's alphas ranged between 0.87 and 0.96 in subsequent studies (Monacis et al, 2016;Pontes et al, 2017;Wu et al, 2017). Consistent with these reliability findings previously reported, the Turkish version obtained similar for the newly developed IGDS9-SF (α = 0.89).…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations